(untitled) (Archives of Clinical Psychiatry, 2007)
OBJECTIVE: To evaluate the impact of spiritual practices in the clinical and behavioural evolution of inpatients with mental disabilities in a health institution. METHOD: Two groups of patients were compared: the experimental group submitted to spiritual practices and the control group. The Interactive Observation Scale for Psychiatric Inpatients (IOSPI) was employed to obtain data. RESULTS: The comparison of control group (n = 20) with the experimental group (n = 20) verified the difference of variation between the groups (p = 0.045), what demonstrates possible benefits of such intervention. CONCLUSIONS: The research confirmed the hypothesis that practical spirituals uses presents positive results on clinical and behavioural evolution of internal patients with mental disabilities.